Determination of Carprofen in the Presence of some Hydrosoluble Vitamins of Group B by HPLC Method - Stan, Georgeta-Simona; Elena Mitoi, Bianca; Mihaila, Andrei; Adriana Badea, Irinel; Y. Aboul-Enein, Hassan (Current Analytical Chemistry, 2015)
A new HPLC method have been developed and validated for simultaneous determination of carprofen, vitamin B1, B6 and B12 in veterinary pharmaceutical preparations medicines. The method used a Hypersil GOLD aQ (250 x 4.6 mm, 5 μm) column, under the following chromatographic conditions: gradient elution, using a mobile phase composed by phosphate buffer (pH 2.65) and methanol as an organic modifier. The mobile phase was delivered at a flow rate of 1 mL/min and the detection was made by photodiode array (PDA) detector at 292 nm. This method was fully validated and applied on available pharmaceutical product. The limit of detection (LOD) and limit of quantitation (LOQ) for vitamin B1 were 0.5ng/mL and 1.5ng/mL respectively while for vitamin B12 were 1ng/mL and 5ng/mL respectively The main advantages of this HPLC method relies on the possibility to asses in a single run all the above mentioned drugs.
Keywords: vitamin B1